(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the formation and development of military strategy and tactics during the reign of Zahiriddin Muhammad Babur and the Baburites, as well as their place in the history of world military art, based on historical sources. The article first of all reveals the historical roots of Babur’s personal military experience, combat activities and strategic decisions. It also covers the role of the military sphere in the Baburite statehood, the organizational structure of the army and the military management system from a scientific point of view.